Multidisciplinary Heart Team Model to Deliver Advanced Cardiovascular Care in a Public Safety‐Net Hospital - Emily K. Zern; Soham Rege; Isaac Gorgy; Wilson Tang; Parth P. Patel; Kelley Benck; Eric D. Lucas; Adriana Shen; Henry Steyer; Imam Sanousi; Brandon B. Ge; Ben A. Lin; et al. (Journal of the American Heart Association, 2026)
Background Implementation of guideline‐supported Multidisciplinary Heart Teams (MHT) for the management of complex cardiovascular disease has not been described in a public safety‐net hospital setting. In May 2023, an MHT was established at Los Angeles General Medical Center to deliver comprehensive cardiovascular care to an underserved population in a resource‐constrained setting. Methods We conducted a retrospective review of all cases discussed by a comprehensive MHT at Los Angeles General Medical Center from May 24, 2023 through January 21, 2026. The MHT convenes weekly in a hybrid format, using a privacy‐compliant centralized platform for longitudinal care coordination. Referral pathways extend to affiliated safety‐net clinics and hospitals. Results During the study period, the MHT discussed 494 patients, including 369 (74.7%) with any valvular disease, 78 (15.8%) with complex coronary disease, 29 (5.9%) with congenital heart disease, and 33 (6.7%) with endocarditis. The patient cohort reflected a high prevalence of health care disparities, with 93.9% reporting a race or ethnicity other than non‐Hispanic White, a high proportion with publicly funded (69.0% Medicaid) or uninsured (3.6%) status, and frequent substance use disorders (28.1%). The MHT generated consensus recommendations including cardiac surgery (99 [20.0%]), transcatheter intervention (122 [24.7%]), complex percutaneous coronary intervention (30 [6.1%]), and medical management (149 [30.2%]). In‐hospital mortality was low among patients who underwent surgical or percutaneous procedure (9 [3.6%]). Programmatic growth included development of a transcatheter valve repair program and increased complexity of cardiac surgical case volume. Conclusions Establishment of an MHT in a resource‐constrained public safety‐net hospital was feasible and sustainable. Our model may serve as a blueprint to deliver guideline‐concordant cardiovascular therapies to underserved populations.